141 PBMC-based cancer vaccines generated with microfluidics squeezing demonstrate synergistic and durable tumor reduction in combination with PD1 checkpoint and FAP targeted IL-2 variants. (9th November 2020) - Booty, Matthew; Stockmann, Adam; Pryor, Olivia; Myint, Melissa; Trumpfheller, Christine; Nicolini, Valeria; Klein, Christian; Codarri, Laura; Umana, Pablo; Sharei, Armon; Bernstein, Howard; Seidl, Katherine; et al.
Abstract : Background: We engineered unfractionated peripheral blood mononuclear cells (PBMCs) to function as antigen presenting cells (APCs) that generate potent CD8+ T cell responses. We investigated the combined efficacy of PBMC-based cancer vaccine with targeted interleukin 2 variants (IL2v); anti-Programmed Cell Death Protein 1 (muPD1-IL2v) and anti-Fibroblast Activation Protein (muFAP-IL2v). Methods: We generated PBMC-based cancer vaccine with microfluidic cell engineering system (Cell Squeeze®), which facilitates direct cytosolic antigen delivery and enables cell subsets within PBMCs to function as APCs. The immunocytokines used contain IL2v fused with antibody counterparts that enable targeting to tumor-associated stroma or immune cells (aFAP and aPD-1, respectively) with modified FcR binding. The IL2v moiety, compared with wild-type IL-2, has abolished binding to IL-2Ra (CD25) resulting in IL-2Rgb binding only, thus fully maintaining activity on NK and CD8+ T cells, while avoiding Treg activity and CD25 mediated toxicity. Results: In the murine TC-1 HPV tumor model, SQZ-PBMC-based vaccines show efficacy as monotherapy (1e6 cells administered iv on day 14 post-tumor implant), while SQZ combination therapy with targeted immunocytokines, muPD1-IL2v and muFAP-IL2v (2 mg/kg or 1 mg/kg, respectively, administered iv on days 21, 28, and 35 post-tumor implant) significantly delayed tumor growth and improved survival in murine TC-1 HPV tumor model. Median survival of combination treated groups remained undefined at day 84 post-tumor implant, while the monotherapy treated groups had calculated median survival times of 36.5, 42, and 70 days for the muFAP-IL2v, muPD1-IL2v, and SQZ monotherapy groups, respectively. Following initial tumor clearance, tumor-free mice (2/12 animals for SQZ monotherapy; 8/12 animals for SQZ with muFAP-IL2v; 11/11 animals for SQZ with muPD1-IL2v) were all re-challenged at day 84 and all remained tumor free at least 7 weeks post re-challenge, suggesting the generation of anti-tumor memory response. In a mechanistic study, SQZ-PBMCs in combination with muPD1-IL2v resulted in increased expansion of intra-tumoral, antigen-specific CD8+ T cells compared with separate administration of either therapy ( 3.6-fold over SQZ alone; 2000-fold over muPD1-IL2v alone; per mg of tumor). Combination therapy also resulted in improved IFNγ and TNFα cytokine production by SQZ-elicited CD8+ T cells ( 1.7-fold and 9-fold, respectively, over SQZ monotherapy). Conclusions: Monotherapy with SQZ-PBMC-based cancer vaccines can drive anti-tumor responses in murine systems. These responses are enhanced by combined administration of targeted immunocytokines. Monotherapy with SQZ-PBMC-HPV is currently under clinical evaluation for HPV16+ tumor indications. These preclinical data support the combination of SQZ-PBMC with FAP-IL2v or PD1-IL2v targeted immunocytokine as promising cancer immunotherapies.